Comparison of rates of opioid withdrawal symptoms and reversal of opioid toxicity in patients treated with two naloxone dosing regimens: a retrospective cohort study. (2nd January 2021) - Purssell, Roy; Godwin, Jesse; Moe, Jessica; Buxton, Jane; Crabtree, Alexis; Kestler, Andrew; DeWitt, Chris; Scheuermeyer, Frank; Erdelyi, Shannon; Balshaw, Robert; Rowe, Adrianna; Cochrane, Christopher K.; et al.
Abstract: Introduction: When managing opioid overdose (OD) patients, the optimal naloxone regimen should rapidly reverse respiratory depression while avoiding opioid withdrawal. Published naloxone administration guidelines have not been empirically validated and most were developed before fentanyl OD was common. In this study, rates of opioid withdrawal symptoms (OW) and reversal of opioid toxicity in patients treated with two naloxone dosing regimens were evaluated. Methods: In this retrospective matched cohort study, health records of patients who experienced an opioid OD treated in two urban emergency departments (ED) during an ongoing fentanyl OD epidemic were reviewed. Definitions for OW and opioid reversal were developed a priori . Low dose naloxone (LDN; ≤0.15 mg) and high dose naloxone (HDN; >0.15 mg) patients were matched in a 1:4 ratio based upon initial respiratory rate (RR). The proportion of patients who developed OW and who met reversal criteria were compared between those treated initially with LDN or HDN. Odds ratios (OR) for OW and opioid reversal were obtained via logistic regression stratified by matched sets and adjusted for age, sex, pre-naloxone GCS, and presence of non-opioid drugs or alcohol. Results: Eighty LDN patients were matched with 299 HDN patients. After adjustment, HDN patients were more likely than LDN patients to have OW after initial dose (OR = 8.43; 95%CI: 1.96, 36.3; p  = 0.004) and after any dose (OR = 2.56; 95%CI: 1.17, 5.60; p  = 0.019). HDN patients were more likely to meet reversal criteria after initial dose (OR = 2.73; 95%CI: 1.19, 6.26; p  = 0.018) and after any dose (OR = 6.07; 95%CI: 1.81, 20.3; p  = 0.003). Conclusions: HDN patients were more likely to have OW but also more likely to meet reversal criteria versus LDN patients.